1974
DOI: 10.1111/j.1476-5381.1974.tb08566.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins, Kinin and Inflammation in the Rat

Abstract: Prostaglandin E1 and bradykinin exert synergistic effects on vascular permeability in rat skin and in rat paws. Prostaglandin E2 is inactive in this respect. Prostaglandin F2α reduces the bradykinin response in rat skin but not in rat paws. It also markedly reduces the response of the skin to dextran, 5‐hydroxytryptamine and histamine. Prostaglandin E1 and dextran exert synergistic effects in rat skin when threshold doses of each agent are used. Rats genetically resistant to dextran fail to respond to intrader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
1

Year Published

1975
1975
1986
1986

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 9 publications
3
9
1
Order By: Relevance
“…Two important characteristics of the inflammatory properties of E prostaglandins are the long duration of action (Juhlin & Michaelsson, 1969;Ferreira, 1972), and their ability to potentiate the effects of other mediators of inflammation (Ferreira, 1972;Williams & Morley, 1973;Ferreira, Moncada & Vane, 1973;Greaves & McDonald-Gibson, 1973;Thomas & West, 1974). We have now shown that the inflammatory effects of prostaglandin D2 show the same two characteristics.…”
Section: Actions Ofpgd2 On Cutaneous Responses To Histamine and Bradysupporting
confidence: 50%
See 1 more Smart Citation
“…Two important characteristics of the inflammatory properties of E prostaglandins are the long duration of action (Juhlin & Michaelsson, 1969;Ferreira, 1972), and their ability to potentiate the effects of other mediators of inflammation (Ferreira, 1972;Williams & Morley, 1973;Ferreira, Moncada & Vane, 1973;Greaves & McDonald-Gibson, 1973;Thomas & West, 1974). We have now shown that the inflammatory effects of prostaglandin D2 show the same two characteristics.…”
Section: Actions Ofpgd2 On Cutaneous Responses To Histamine and Bradysupporting
confidence: 50%
“…Intradermal injections of prostaglandin E1 produce a long-lasting erythema (Solomon, Juhlin & Kirschbaum, 1968;Juhlin & Michaelson, 1969) and hyperalgesia (Ferreira, 1972) and potentiate the increase in vascular permeability (Williams & Morley, 1973;Moncada, Ferreira & Vane, 1973; Thomas & West, 1974), pain (Ferreira, 1972) and itching (Greaves & McDonald-Gibson, 1973) produced by bradykinin or histamine. Increased amounts ofE prostaglandin are found in inflamed skin (Sondergaard & Greaves, 1970;Greaves, Sondergaard & McDonald-Gibson, 1971; Angaard & Jonsson, 1971;Hamberg & Jonsson, 1973), in ocular (Eakins, Whitelocke, Perkins, Bennet & Ungar, 1972) and in many other types of inflammation (Ferreira, Flower, Moncada & Vane, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Such a mechanism would explain why in the present experiments, NA-induced constrictor responses obtained in the presence and absence of external calcium were not significantly different in the short run. PGE2 in low doses can cause depolarization of smooth muscle cells (Suzuki, Osa & Kuriyama, 1976) and increase membrane permeability (Horton, 1963;Crunkhorn & Willis, 1971;Thomas & West 1974). The mechanism of PGE2 potentiation of NA vasoconstriction may be explained as follows: NA in the presence of PGE2 activates the pharmacomechanical pathway, but in addition, NA vasoconstriction involves calcium from the external medium, either because PGE2 increases membrane permeability to calcium or because PGE2 enables NA to cause depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…Of these mediators, it is well known that histamine and slow reacting substance of anaphylaxis (SRS-A) play important roles. Fur thermore, serotonin also plays an important role in rodents.SRS-A, which produces a potent and long-lasting contraction of smooth muscles, has been demon strated to be a mixture of leukotrienes C4 (LTC4), D4 (LTD4) and E4 (LTE4), metabolites from arachidonic acid [2-6], Recently, it was indicated that these LTs have potent activities to increase the vascular permea bility in guinea pigs, rats and hamsters [7][8][9][10],In addition it was reported that the E series of pros taglandins (PGs), PGD2 and PGIi potentiate the in crease of vascular permeability caused by histamine, bradykinin, LTB4, LTC4 and LTD4 in human, mon keys, guinea pigs, rats and rabbits [11][12][13][14][15][16][17][18]. PGs are also metabolites from arachidonic acid.…”
mentioning
confidence: 99%